2023
DOI: 10.3390/ijerph20021258
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Refraction of Two Myopia Control Contact Lens Models in a Young Myopic Population

Abstract: Peripheral refraction can lead to the development of myopia. The aim of this study was to compare relative peripheral refraction (RPR) in the same cohort of uncorrected (WCL) and corrected eyes with two different soft contact lenses (CL) designed for myopia control, and to analyze RPR depending on the patient’s refraction. A total of 228 myopic eyes (114 healthy adult subjects) (−0.25 D to −10.00 D) were included. Open-field autorefraction was used to measure on- and off- axis refractions when uncorrected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…found that eyes with low myopia had relative peripheral hyperopia only at 30° in the TVF and NVF, whereas those with moderate and high myopia had relative peripheral hyperopia at all eccentricities. Similar findings were reported by Marcellán et al 34 . They observed a statistically significant, increasing linear trend in RPR measured at 30° eccentricities (nasal and temporal) with respect to the degree of myopia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…found that eyes with low myopia had relative peripheral hyperopia only at 30° in the TVF and NVF, whereas those with moderate and high myopia had relative peripheral hyperopia at all eccentricities. Similar findings were reported by Marcellán et al 34 . They observed a statistically significant, increasing linear trend in RPR measured at 30° eccentricities (nasal and temporal) with respect to the degree of myopia.…”
Section: Discussionsupporting
confidence: 90%
“…7,[31][32][33] We found asymmetry between nasal and temporal eccentricities at the same peripheral location for each lighting condition, although the result was not significant (all p > 0.89). Marcellán et al 34 recently reported that the RPR was less hyperopic for the TVF than the NVF, but again, the difference was not statistically significant. Mutti et al 7 also found a hyperopic (although asymmetric) increase in the temporal and nasal retinas of Caucasian patients.…”
Section: Rpr Across the Visual Field For Each Lighting Conditionmentioning
confidence: 89%